Effectiveness of repeated structured teaching programme on knowledge regarding fluid and dietary compliance and its effect on biochemical parameters and interdialysis weight gain among patients undergoing hemodialysis - Chettri, Roshni (Indian Journal of Nursing Sciences, 2024)
The study conducted was aimed to assess the knowledge, effectiveness of structured teaching programme regarding fluid and dietary compliance and find an association between the knowledge score with biochemical parameters and interdialysis weight gain. Methods and materials: The research design selected for the study was Quasi Experimental time series design with control group. The samples comprised of 60 patients selected by Non-probability purposive sampling technique and 30 samples each were allotted to experimental and control groups receiving hemodialysis. The pre-test and 3 times posttest knowledge scores were assessed using self - structured knowledge questionnaires. The teaching program was administered to the experimental group only, for 3 times. The weight (interdialysis) for both the experimental and the control groups were recorded. The biochemical parameters were also extracted from patient medical records. Results: The mean percentage and SD of pre-test score for experimental group were 66.38% and 2.132 respectively. The mean percentage and SD of pre-test score for control group were 65.13% and 2.059 respectively. Experimental group after receiving repeated structured teaching, the mean percentage and SD for post-test 1, post-test 2 and post-test 3 were (84.71%, 2.368), (94.46%, 1.398) and (97.50%, 2.027) respectively. This illustrated a significant improvement in the knowledge. There was no significant association between pre-test knowledge scores of the respondents with selected demographic variables. There was no significant association between knowledge scores, interdialysis weight and biochemical parameters for experimental group. The r-ANOVA done for tests of between-subjects effects predicted a significant difference between the two groups, calculated F(3,174)=87.158, P<0.001. Conclusion: The study revealed that inspite of highly effective Repeated Teaching Programme in improving the knowledge, the compliance regarding fluid and diet were lacking.